Multitarget compounds bearing tacrine- and donepezil-like structural and functional motifs for the potential treatment of Alzheimer's disease. (April 2017) - Ismaili, Lhassane; Refouvelet, Bernard; Benchekroun, Mohamed; Brogi, Simone; Brindisi, Margherita; Gemma, Sandra; Campiani, Giuseppe; Filipic, Slavica; Agbaba, Danica; Esteban, Gerard; Unzeta, Mercedes; Nikolic, Katarina; et al.
Highlights: Recent advances in multitarget ligands designed for developing potential AD therapeutics. Tacrine and donepezil hybrids able to interfere with AD related neurodegeneration. Multitarget compounds as potential disease-modifying anti-Alzheimer's drugs (DMAAD). Multitarget compounds as potential therapeutics for a multifactorial disease as AD. Abstract: Alzheimer's disease is a multifactorial and fatal neurodegenerative disorder characterized by decline of cholinergic function, deregulation of other neurotransmitter systems, β-amyloid fibril deposition, and β-amyloid oligomers formation. Based on the involvement of a relevant number of biological systems in Alzheimer's disease progression, multitarget compounds may enable therapeutic efficacy. Accordingly, compounds possessing, besides anticholinergic activity and β-amyloid aggregation inhibition properties, metal chelating and/or nitric oxide releasing properties with additional antioxidant capacity were developed. Other targets relevant to Alzheimer's disease have also been considered in the last years for producing multitarget compounds such as β-secretase, monoamino oxidases, serotonin receptors and sigma 1 receptors. The purpose of this review will be to highlight recent reports on the development of multitarget compounds for Alzheimer's disease published within the last years focusing on multifunctional ligands characterized by tacrine-like and donepezil-like structures.